Clinical efficacy of combination therapy of an immune checkpoint inhibitor with taxane plus platinum versus an immune checkpoint inhibitor with fluorouracil plus platinum in the first-line treatment of patients with locally advanced, metastatic, or recurrent esophageal squamous cell carcinoma - Li, Ying; Ji, Yanyan; Shen, Lin; Yin, Xudong; Huang, Tianyu; Deng, Bin; Guo, Hong; Wu, Yunjiang; Chen, Yong (Frontiers in Oncology, 2022)
Background Chemotherapy combined with immune checkpoints inhibitors (ICIs) has been established as a standard treatment for locally advanced, metastatic, or recurrent esophageal squamous cell cancer (ESCC). However, the optimal chemotherapy regimen in combination therapy is still unclear. Purpose To investigate the efficacy and adverse events of the fluorouracil plus platinum (FP) and taxane plus platinum (TP) regimens in ESCC patients receiving chemo-immunotherapy, we conducted this systematic review and meta-analysis. Methods Potentially eligible studies were searched from Medline, Embase, Web of Science, and the Cochrane Library. Pooled rates of overall response rate (ORR), disease control rate (DCR), overall survival (OS), progression-free survival (PFS), and adverse events were compared between ICIs+TP and ICIs+FP groups in ESCC patients receiving first-line chemo-immunotherapy. Results A total of 10 clinical trials were included, of which 5 were randomized controlled trials. Compared with chemotherapy alone, chemo-immunotherapy significantly improved the OS of ESCC patients (pooled HR=0.69; 95% CI, 0.63–0.76; p<0.01). Pooled analysis revealed that ESCC patients receiving ICIs+TP had significantly higher ORR, DCR, PFS, and OS rates than those receiving ICIs+FP. No statistically significant difference in the pooled incidence rate of treatment-related death was found (2.3% vs 0.9%, P=0.08). ICIs+TP had significantly higher rates of hematologic toxicity but lower rates of gastrointestinal toxicity than ICIs+FP. Conclusions Based on the current data, the first-line treatment using ICIs+TP may be a better option than ICIs+FP in advanced, metastatic, or recurrent ESCC.